CLIMATE CHANGES AND CIVIL LAW - Elements for an Adaptation Strategy - Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In recent days, the need for systematically dealing with the chalanges, which appear in relation to environment protection and sustainable development is ever more frequently pointed to. In the center of that problematics are climate changes and their effects. The work points out the fact that the climate is changing due to human activities, as well as the laws of nature which have been formulated by Milutin Milankovic. In this regard, society should put organized work into eliminating the anthropogenic factors, while simultaneously adapting to the climate changes that are inevitable. The European Union has adopted a special Strategy for adaptation to climate changes. That document defines guidlines for development of public policies and operative measures in different areas. Similar (national) strategies have been adopted by certain countries. Efficient application of strategic documents and public policies is not possible without adequate legal regulative. Law traditionally comes late, as compared to social needs, including those related to reacting to climate changes and their effects. The work points out the need for civil law to be adapted to current trends. The author thinks that redifining the property rights are inevitable, and that it will be, due to climate changes, further restricted, in public interest, and for the sake of protection of existential interests of individuals and smaller social groups, alike. In this regard, thinkings of certain European and American authors on social function of that and other institutes of private law have been pointed out. In order for a higher level of social cohesion to be acheaved in crisis situations, legal regulative should be harmonized with moral rules to a greater extent. Society should create a more just law, while individuals should apply it with more mutual understanding and solidarity. The author thinks that the traditional imission law should be transformed as well. Rules on imission should not be directed only to protection of private interests, but also to protection of public interests. In this regard, responsibility should not be bound only to unallowed influence on neighboring property, but should be expanded to cases in which someone emits into environment something that poses a threat to a wider community.  The work also points out the need to more precisely regulate problems regarding erosion of soil, changing of water flows, servitudes, etc.
Keywords: imission; property law; strategy of adaption; civil law; climate changes; sustainable development; environment protection